2019
DOI: 10.1111/jce.14150
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between time‐to‐isolation and freeze duration: Computational modeling of dosing for Arctic Front Advance and Arctic Front Advance Pro cryoballoons

Abstract: BackgroundPreclinical and clinical studies have utilized periprocedural parameters to optimize cryoballoon ablation dosing, including acute time‐to‐isolation (TTI) of the pulmonary vein, balloon rate of freezing, balloon nadir temperature, and balloon‐thawing time. This study sought to predict the Arctic Front Advance (AFA) vs Arctic Front Advance Pro (AFA Pro) ablation durations required for transmural pulmonary vein isolation at varied tissue depths.MethodsA cardiac‐specific, three‐dimensional computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…It identified that for a PV tissue thickness of 3 mm, a TTI of w60 seconds required a total ablation time of w160 seconds for full, circumferential, and transmural penetration of lethal temperature (220 C) into the cardiac tissue. 41 These computational data closely mirror the clinical paradigms that have reported successful outcomes of TTI-guided dosing described in the previous sections. Having said that, this computational model was premised on a circular PV morphology with homogeneous tissue composition and depth.…”
Section: E Future Considerations and Limitations Of Cryoballoon Dosing E1 Translating Preclinical Observations To Clinical Practicesupporting
confidence: 72%
See 1 more Smart Citation
“…It identified that for a PV tissue thickness of 3 mm, a TTI of w60 seconds required a total ablation time of w160 seconds for full, circumferential, and transmural penetration of lethal temperature (220 C) into the cardiac tissue. 41 These computational data closely mirror the clinical paradigms that have reported successful outcomes of TTI-guided dosing described in the previous sections. Having said that, this computational model was premised on a circular PV morphology with homogeneous tissue composition and depth.…”
Section: E Future Considerations and Limitations Of Cryoballoon Dosing E1 Translating Preclinical Observations To Clinical Practicesupporting
confidence: 72%
“…Computational modeling may help bridge the gaps between basic science, preclinical research, and clinical observations while generating hypotheses that can be tested in clinical trials. In a recent publication, Getman et al 41 leveraged fundamental understandings of cellular responses to cryothermal energy in order to determine the required duration of cryoablation using Arctic Front Advance and Arctic Front Advance Pro catheters. The model calculated the predicted TTI and the total freeze duration required to achieve circumferential, transmural PVI at varying PV tissue depths.…”
Section: E Future Considerations and Limitations Of Cryoballoon Dosing E1 Translating Preclinical Observations To Clinical Practicementioning
confidence: 99%
“…Importantly, significant differences in the biophysical parameters (i.e., rate of cooling, cryoballoon nadir temperatures, thaw times) during cryoablation with the two technologies were reported. Biophysical characteristics during ablation with the Arctic Front Advance cryoballoon have been carefully evaluated via preclinical studies, computational modeling, and randomized controlled trials over the last 15 years and have been used to define dosing algorithms and best practices 2–5 . Despite the similarities between the two cryoballoons, results from this study suggest the PolaRx balloon has unique biophysical parameters and may need ongoing investigation to optimize dosing.…”
mentioning
confidence: 99%
“…Biophysical characteristics during ablation with the Arctic Front Advance cryoballoon have been carefully evaluated via pre-clinical studies, computational modeling, and randomized controlled trials over the last 15 years and have been used to define dosing algorithms and best practices. [2][3][4][5] Despite the similarities between the two cryoballoons, results from this study suggest the PolaRx balloon has unique biophysical parameters and may need ongoing investigation to optimize dosing.…”
Section: Funding: Nonementioning
confidence: 88%